2022
DOI: 10.1038/s41467-022-31159-w
|View full text |Cite
|
Sign up to set email alerts
|

Anderson transition in stoichiometric Fe2VAl: high thermoelectric performance from impurity bands

Abstract: Discovered more than 200 years ago in 1821, thermoelectricity is nowadays of global interest as it enables direct interconversion of thermal and electrical energy via the Seebeck/Peltier effect. In their seminal work, Mahan and Sofo mathematically derived the conditions for ’the best thermoelectric’—a delta-distribution-shaped electronic transport function, where charge carriers contribute to transport only in an infinitely narrow energy interval. So far, however, only approximations to this concept were expec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 70 publications
(73 reference statements)
4
29
2
Order By: Relevance
“…For the n-type film showing the highest P F , n is close to −10 22 cm –3 . This high value remains within the range of carrier concentrations obtained in the literature on Fe 2+x V 1+y Al 1+z , showing the power factor ranging from 2 to 7.6 mW/K 2 m. , …”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…For the n-type film showing the highest P F , n is close to −10 22 cm –3 . This high value remains within the range of carrier concentrations obtained in the literature on Fe 2+x V 1+y Al 1+z , showing the power factor ranging from 2 to 7.6 mW/K 2 m. , …”
Section: Resultssupporting
confidence: 82%
“…It corresponds to twice the maximum power factor obtained at 350 K by Mikami et al in Ti-substituted Fe 2 VAl thin films and at 300 K by Kudo et al in Fe 2–x V 1+x Al films grown by the MBE technique . It should be mentioned that our results are close to the highest values obtained in Fe 2 VAl-based alloys in the bulk state with P F = 7.6 mW/K 2 m recently obtained at 300 K in a 1653 K-quenched stoichiometric Fe 2 VAl sample or P F = 6.7 mW/K 2 m reported in bulk n-type Fe 1.98 V 1.02 Al 0.9 Si 0.1 at 300 K and Fe 2 V 1.03 Al 0.97 at 250 K.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Only recently, it has been demonstrated that the electronic structure itself can be severely modified, exhibiting remarkable tune-ability. By either opening the band gap [291] or incorporating narrow resonant or semi-localized impurity states at E F [292,293], the Seebeck coefficient was significantly enhanced, compared to the conventional S(n) behaviour (see coloured symbols, deviating from the black solid line in figure 48). Consequently, thermoelectric power factors 2-3 times larger than those of optimized Bi 2 Te 3 systems in the 0 • C-100 • C range have been achieved [291].…”
Section: Statusmentioning
confidence: 99%